Confidence in consent: the use of a patient information leaflet as a tool for consent for regional anaesthesia – a service improvement project - Emma Lennon; Shanika Wijayaratne; Abigail Walsh; Sherife El Mahgoub (BMJ Open Quality)
Regional anaesthesia is increasingly used for perioperative pain management, offering benefits such as improved pain scores, reduced opioid use and early mobilisation. However, informed consent remains a critical issue, particularly given the rising litigation claims related to peripheral nerve blockade. This service improvement project evaluates the impact of introducing a patient information leaflet (PIL) on patient understanding and experience of the consent process. A structured in-person survey was administered pre and post intervention to two cohorts of 30 patients each. The results demonstrate improvements in patient recall of risks and benefits, understanding of voluntary consent and overall satisfaction with the consent process. The findings are suggestive that PILs enhance shared decision-making and should be integrated into standard consent procedures.